2020
DOI: 10.1016/j.isci.2020.101045
|View full text |Cite
|
Sign up to set email alerts
|

Reference and Ghost Proteins Identification in Rat C6 Glioma Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) mediate intercellular communication and regulate a broad range of biological processes. Novel therapeutic strategies have emerged based on the use of EVs as biological nanoparticles. To separate isolated EVs from protein aggregates and the external part of EVs membrane proteins, we performed a Trypsin/Lys C digestion treatment of EVs pellets, followed by Amicon filtration. After these steps, all the fractions have been subjected to proteomic analyses. Comparison between 6 h Trypsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The ARCN1 protein is mainly expressed in inflamed tissues 46 . Another BPI-induced gene, VPS37b, is recently reported as a surface protein on the glioma-derived exosomes 47 . It is possible that the BPI-ARCN1 axis or BPI-VPS37b axis in T cells facilitates exosome formation, leading to inflammatory exosome infiltration into target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The ARCN1 protein is mainly expressed in inflamed tissues 46 . Another BPI-induced gene, VPS37b, is recently reported as a surface protein on the glioma-derived exosomes 47 . It is possible that the BPI-ARCN1 axis or BPI-VPS37b axis in T cells facilitates exosome formation, leading to inflammatory exosome infiltration into target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…170 alternative proteins (AltProts) were found significantly variable in the three groups identified above. If the function of these AltProts are still poorly understood, it has been shown that they can have a role in regulation of transcription and can also be present in extracellular vesicles (77). Finally, more than 50% of the AltProts identified in the present study come from the translation of ncRNAs transcribed from pseudogenes.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several studies have focused on the use of EVs as biomarkers to obtain information about the presence and/or the molecular evolution of neoplastic diseases (Le Rhun et al, 2020 ; Murgoci et al, 2020a ). In addition, the use of EVs for glioma therapy has been explored.…”
Section: Possible Therapeutic Strategies For Cns Disorders Based On Ementioning
confidence: 99%